Variability of Electromyographic Spectral Measures in Non-fatigued Shoulder Muscles and Implications for Assessing Muscle Fatigue. Issue 2 (3rd April 2019) - Nasser Alasim, Hamad; Nimbarte, Ashish D.
OCCUPATIONAL APPLICATIONS: A declining trend in the electromyographic spectral measures—typically the mean (MnPF) or median (MdPF) frequency—is associated with the development of localized muscle fatigue (LMF). Results of this study indicate that MnPF and MdPF obtained from non-fatigued shoulder muscles can vary/decline by up to 5%–6% due to changes in the level and direction of force applied at the hand. Thus, a decline in MnPF and MdPF values may not always indicate the development of LMF. It is therefore important that the researchers and the practitioners consider the inherent variability in the electromyographic spectral measures to improve their approaches to quantifying LMF. TECHNICAL ABSTRACT Background : Quantification of localized muscle fatigue (LMF) plays an important role in understanding the causation and contributing to the prevention of work-related musculoskeletal disorders. A shift in the power spectrum of the electromyographic (EMG) signal, typically measured using a decrease in mean (MnPF) or median (MdPF) frequency, has been used frequently to quantify LMF. Work-related factors, though, can also produce such EMG spectral shifts, however only a handful of studies have tested the effect of work-related factors on the variability in the spectral content of EMG signals. Purpose : This study investigated the impact of the level and direction of hand force application on the variability of MnPF and MdPF obtained from non-fatigued shoulder muscles. Method : Ten male participants performed 30 randomized experimental trials using their right arm at three force levels, in five force directions, with two repetitions in each condition. Results : Variation in MnPF values was ∼2%–5% due to changes in the level and direction of force application. The corresponding variations for MdPF values were ∼2%–6%. Conclusions : These results indicate that inherent variability exists in MnPF and MdPF under no-fatigue conditions. Therefore, for studies that utilize LMF as a surrogate measure of injury risk, it is critical that EMG spectral variability be quantified and then used carefully to support any conclusions.